The relationship between parenting patterns of parents and peer groups with attitudes in persiapan adolescent high school students stabat distric - Nurhikmah Panjaitan (Institute of Computer Science (IOCS), 2022)
Adolescence is a period of transition from children to adulthood which is characterized by unstable emotions and still trying to find identity. Adolescents will try to free themselves from parental pressure to be aggressive towards something that is contrary to themselves. In educating children, parents can provide non-formal education such as giving attention, affection, supervision and guidance.. To find out the relationship between parenting style and peer group, with the attitude of adolescents in the Academic Year Stabat Preparatory High School. This type of research is descriptive correlational with a sample of 40 people. The results of the research on the relationship between parenting parents and attitudes in adolescents obtained data on authoritarian parenting patterns, the majority with good attitudes of adolescents as many as 11 respondents (27.5%) and with attitudes of teenagers who were not good as many as 10 people (25%), the test results statistics Pvalue 0.761 and df value 1, and the relationship between peer group relationships with good attitudes of adolescents as many as 11 respondents (27.5%) and with attitudes of adolescents who are not good as many as 10 people (25%) obtained a Pvalue 0.761 and df value 1. The conclusion of this study is that there is no significant relationship between parenting style and peer group association with attitudes in adolescents.